1997
DOI: 10.1076/brhm.28.3.5.39.13131
|View full text |Cite
|
Sign up to set email alerts
|

Daylight and Artificial Light Phase Response Curves for the Circadian Rhythm in Locomotor Activity of the Field Mouse Mus booduga

Abstract: The sensitivity of the circadian pacemaker of the field mouse Mus booduga to diffuse daylight pulses of 15 min duration and 1000 lux intensity was measured in a series of experiments and a phase response curve (PRC) constructed. The PRC evoked was of type-I with significant quantitative differences compared to the PRCs constructed for other light stimuli (fluorescent and incandescent light sources) of the same intensity and duration. Not only are the advance and delay peaks larger in the daylight PRC, but ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Melatonin production is similarly reduced in rats under nighttime light levels of 0.2 lux (Dauchy et al, 1997), and in hamsters at levels above 1 lux (Brainard et al, 1982), and has been shown to suppress immune responses and increase the rate of tumour growth (Dauchy et al, 1997;Bedrosian et al, 2011b). Similar Sharma et al (1997) *Converted from reported values in foot candles. Note that: (i) in many cases these represent levels of experimental treatments, and precisely where thresholds might lie remains unknown; and (ii) although widely used, lux measurement places emphasis on brightness at wavelengths perceived by human vision.…”
Section: (1) Circadian Clocks and Photoperiodismmentioning
confidence: 96%
“…Melatonin production is similarly reduced in rats under nighttime light levels of 0.2 lux (Dauchy et al, 1997), and in hamsters at levels above 1 lux (Brainard et al, 1982), and has been shown to suppress immune responses and increase the rate of tumour growth (Dauchy et al, 1997;Bedrosian et al, 2011b). Similar Sharma et al (1997) *Converted from reported values in foot candles. Note that: (i) in many cases these represent levels of experimental treatments, and precisely where thresholds might lie remains unknown; and (ii) although widely used, lux measurement places emphasis on brightness at wavelengths perceived by human vision.…”
Section: (1) Circadian Clocks and Photoperiodismmentioning
confidence: 96%
“…hooduga remains sensitive to melatonin throughout the subjective day, thus exhibiting a lack of a distinctive refractory zone. A higher dose of melatonin (10 mg/kg) evokes phase shifts of magnitude comparable to the magnitude of lightinduced phase shifts (Sharma et al, 1997).…”
Section: Resultsmentioning
confidence: 92%
“…The field mouse Milts hooduga was chosen for the present study because of its precise, robust, and easily measured circadian rhythm in locomotor activity. The response of activity rhythm to light stimuli has also been well studied in these mice [Sharma, 1996;Sharma and Chandrashekaran, 1997;Sharma et al, 19971. The lightinduced PRC is of type-1, with delays dominating during early subjective night, advances during late subjective night, and minimal but non-zero phase shifts during the subjective day [Sharma et al, 19971.…”
Section: Introductionmentioning
confidence: 99%
“…2) along with a unique shape of the phase response curve evoked by light [8,9] could possibly explain the functional importance of the dependency of clock precision on the free-running period. 2) along with a unique shape of the phase response curve evoked by light [8,9] could possibly explain the functional importance of the dependency of clock precision on the free-running period.…”
Section: Precision Of a Mammalian Circadian Clockmentioning
confidence: 99%